Are sovereign wealth fund investments destabilizing? - Pang, Andy Shang Yuan (2011)
Sovereign Wealth Funds are growing in number and in size recently. Their investments have spread globally and they are now a major investor in the world. The investing decisions of Sovereign Wealth Funds can potentially affect both the fundamentals of an individual stock such as its risk profile and value, and also the global market as a whole. Jen [2007] estimated that should these investors decide to invest a significant part of their current holding of US$5.6 trillion worth of assets, it could raise the global P/E ratio by up to 10%. The major influence of Sovereign Wealth Funds poses a question to investors worldwide - would the rise of Sovereign Wealth Funds and their investments bring about additional volatility to the markets?